The Effect of Cash Holding Policy, Dividend Policy and Profitability on Stock Prices - Humaira, Adisa; Humaira, Adisa; Susanto, Hendro (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2020)
Increased non-resident ownership makes the capital market vulnerable to declining stability and the global economy that can affect the condition of the financial sector as indicated. These factors will affect the company's stock price is the company's cash holding policy, dividend policy and profitability performance. This study aims to determine the effect of cash holding policy, dividend policy and profitability on the company's stock price. Cash holding policy variables are measured by a cash to asset ratio, dividend policy is measured by a dividend payout ratio, profitability is measured by return on equity (ROE) and stock prices are measured by a price to book ratio. This research is a quantitative study using multiple regression analysis methods. The data used are secondary data from the annual report and the stock market performance reports of financial sector companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling with an observation period of 2011 - 2017 and there are 14 companies that meet the criteria. The results showed that cash holding and profitability policies had a significant effect on stock prices dividend policy had no significant effect on stock prices.